TMIC-60. COMPREHENSIVE SPATIAL CHARACTERIZATION OF IMMUNE CELLS IN THE CNS BRAIN TUMOR MICROENVIRONMENT. (11th November 2019) - Kassab, Cynthia; Zamler, Daniel; Gupta, Pravesh; Srinivasan, Visish; Rao, Ganesh; Prabhu, Sujit; Huse, Jason; Fuller, Greg; Bruner, Janet; Langford, Lauren; McCutcheon, Ian; Ferguson, Sherise; et al.
Abstract: Previous immune profiling in brain tumors has mostly focused on the high-density tumor areas, and as such, little is known about the nature and types of immunological responses that occur across the tumor landscape, including at the tumor-central nervous system (CNS) interface. En bloc resections of glioblastomas (n=10) and CNS lung metastases (n=10) were oriented on slides as whole mount wedges spanning three anatomical areas including the invasive edge, tumor region, and necrotic core. Tumor segmentation was performed and regional differences were immunologically analyzed for 770 immune genes using the NanoString nCounter System with CIBERSORT analysis to delineate immune gene signatures. The analysis was validated using multiplex immunohistochemistry (IHC). The top upregulated immune genes in the GBM necrotic core were associated with macrophages, including the CD163 lineage marker, chemotactic factors (such as CCL18 and SAA1), and the phagocytosis stimulatory factors (such as IL-8 and MARCO). The necrotic core downregulates GBM antigens (such as IL13RA2 and MAGEB2), markers of dendritic cells (such as LILRA4), and immune stimulatory processes including MHC, IFN, IL-12, TNF, and ICOS expression. In direct contrast, the infiltrating edge of the GBM relative to the tumor is enriched with stimulators for NK cytotoxicity (i.e., CD244, the fractalkine receptor for immune cells), chemokines for thymocytes and dendritic cells, and immune stimulatory IL-12 receptors. Glioblastoma has rare focal isolated areas of CD3 T-cell reactivity within the tumor. Similar to GBM, the necrotic center of lung metastases is enriched in immune suppressive macrophages, as reflected by CD163 IHC staining and arginase expression; however, they are more frequently infiltrated with M1 macrophages. Yet the majority of lung cancers are more diffusely infiltrated with CD3 T cells, especially at the infiltrating edge. In general, we noted distinct inter- and intratumoral immune gene signatures, with macrophages dominating the brain tumors, especially the necrotic core.